Caring for Unbefriended Older Adults and Adult Orphans: A Clinician Survey. Issue 4 (8th August 2021) - Farrell, Timothy W.; Catlin, Casey; Chodos, Anna H.; Naik, Aanand D.; Widera, Eric; Moye, Jennifer
ABSTRACT: Objectives : Unbefriended older adults are those who lack the capacity to make medical decisions and do not have a completed advance directive that can guide treatment decisions or a surrogate decision maker. Adult orphans are those who retain medical decision-making capacity but are at risk of becoming unbefriended due to lack of a completed advance health care directive and lack of a surrogate decision maker. In a follow-up to the 2016 American Geriatrics Society (AGS) position statement on unbefriended older adults, we examined clinicians' experiences in caring for unbefriended older adults and adult orphans. Methods : Clinicians recruited through the AGS (N = 122) completed an online survey about their experiences with unbefriended older adults regarding the perceived frequency of contact, clinical concerns, practice strategies, and terminology; and also with adult orphans regarding the perceived frequency of contact, methods of identification, and terminology. Results : Almost all inpatient (95.9%) and outpatient (86.4%) clinicians in this sample encounter unbefriended older adults at least quarterly and 92.2% of outpatient clinicians encounter adult orphans at least quarterly. Concerns about safety (95.9%), medication self-management (90.4%), and advance care planning (86.3%) bring unbefriended older adults to outpatient clinicians' attention "sometimes" to "frequently." Prolonged hospital stays (87.7%) and delays in transitioning to end-of-life care (85.7%) bring unbefriended older adults to inpatient clinicians' attention "sometimes" to "frequently." Clinicians apply a wide range of practice strategies to these populations. Participants suggested alternative terminology to replace "unbefriended" and "adult orphan." Conclusions : This study suggests that unbefriended older adults are frequently encountered in geriatrics practice, both in the inpatient and outpatient settings, and that there is widespread awareness of adult orphans in the outpatient setting. Clinicians' awareness of both groups suggests avenues for intervention and prevention. Clinical Implications : Health care professionals in geriatric settings will likely encounter older adults in need of advocates. Clinicians, attorneys, and policymakers should collaborate to improve early detection and to meet the needs of this vulnerable population.